2018
DOI: 10.3390/cli6030062
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Earth’s Energy Budget during and after the “Pause” in Global Warming: An Observational Perspective

Abstract: This study examines changes in Earth's energy budget during and after the global warming "pause" (or "hiatus") using observations from the Clouds and the Earth's Radiant Energy System. We find a marked 0.83 ± 0.41 Wm −2 reduction in global mean reflected shortwave (SW) top-of-atmosphere (TOA) flux during the three years following the hiatus that results in an increase in net energy into the climate system. A partial radiative perturbation analysis reveals that decreases in low cloud cover are the primary drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 57 publications
6
87
0
Order By: Relevance
“…Loeb et al [44] have carried out encompassing analyses between the cloud data of CERES [25] and the SW anomalies and they found that the correlation was 0.66 between the global SW anomalies and low level cloud variations that supports the cause-and-effect mechanism.…”
Section: Sw Radiation Anomalies In Climate Zones(b) Temperature Anommentioning
confidence: 99%
See 1 more Smart Citation
“…Loeb et al [44] have carried out encompassing analyses between the cloud data of CERES [25] and the SW anomalies and they found that the correlation was 0.66 between the global SW anomalies and low level cloud variations that supports the cause-and-effect mechanism.…”
Section: Sw Radiation Anomalies In Climate Zones(b) Temperature Anommentioning
confidence: 99%
“…Loeb et al [44] found a significant reduction of 0.83 ± 0.41 Wm -2 in global mean reflected SW flux at the top-of-atmosphere (TOA) flux during the years 2014-2017 after the pause resulting in an increase in net energy into the climate system. Decreases in low cloud cover were the primary driver of the decrease in reflected SW TOA flux.…”
Section: Introductionmentioning
confidence: 99%
“…From days to interannual time scales, EEI variations are dominated by the effects of internal climate modes of variability such as the El Niño Southern Oscillation (Loeb et al, 2018a). Primary causes for variability on decadal and longer time scales are changes in solar irradiance, large volcanic eruptions and natural variations in GHG concentrations (Hansen et al, 2011;von Schuckmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…First, EEI can be directly measured by estimating the global budget of incoming and outgoing radiation at TOA. The current implementation of this method with the Clouds and the Earth's Radiant Energy System (CERES) instruments allows accurate determination of the time variations of EEI (with an uncertainty of ±0.17 Wm −2 at monthly time scales, Loeb et al, 2018a). But the accuracy on the absolute global mean value of EEI is limited within ±4 Wm −2 mainly due to instrument calibration uncertainty (Loeb et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…The large positive anomalies in shortwave TOA flux coincide with positive anomalies in the Arctic sea ice coverage during the early 2000s (Hartmann and Ceppi 2014). In another study, Loeb, Thorsen, et al (2018) assessed the impacts of the climate warming hiatus and found a marked 0.83 ± 0.41 Wm −2 reduction in global reflected shortwave TOA flux during 2000-2017 compared to the hiatus reference years from 2000 to 2014 due to changes in low cloud cover. The seasonal cycles of planetary albedo are largely influenced by surface albedo (Stephens et al 2015).…”
Section: Planetary Albedo/ Reflected Shortwave Radiationmentioning
confidence: 93%